1992
DOI: 10.1073/pnas.89.12.5216
|View full text |Cite
|
Sign up to set email alerts
|

Direct effect of basic fibroblast growth factor on gene transcription in a cell-free system.

Abstract: Recent findings on the translocation of intact fibroblast growth factor (FGF) into the cell nucleus suggest that it functions directly in nuclear events. We examined the effect of human basic FGF (bFGF) on gene transcription in a cell-free system. When mouse genes encoding phosphoglycerate kinases 1 and 2 (Pgk-1 and Pgk-2) were transcribed by using nuclear extracts of Ehrlich ascites tumor cells, FGF affected transcription in different ways: in the presence of bFGF, transcription of the Pgk-1 gene was inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
2

Year Published

1994
1994
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 45 publications
1
49
2
Order By: Relevance
“…Further studies are necessary to assess more precisely the mechanism of induction of pS2 protein by use of the nuclear run-on assay. Recently, bFGF, which has its receptor on the surface of the plasma membrane, was shown to become localized in the nucleus as its functional form in many cultured cells and tissues and to directly regulate the transcription of some genes in a cell-free system [31]. But the present results ruled out the possibility that bFGF directly regulates the transcription of pS2 gene in the nuclei of MCF-7 cells.…”
Section: Discussioncontrasting
confidence: 70%
“…Further studies are necessary to assess more precisely the mechanism of induction of pS2 protein by use of the nuclear run-on assay. Recently, bFGF, which has its receptor on the surface of the plasma membrane, was shown to become localized in the nucleus as its functional form in many cultured cells and tissues and to directly regulate the transcription of some genes in a cell-free system [31]. But the present results ruled out the possibility that bFGF directly regulates the transcription of pS2 gene in the nuclei of MCF-7 cells.…”
Section: Discussioncontrasting
confidence: 70%
“…This suggests that there is concomitant expression of basic FGF and FGF receptor in pancreatic ductal adenocarcinomas, which may allow for excessive autocrine growth stimulation. Furthermore, eight (25%) tumours had nuclear staining for basic FGF, supporting the concept of an intracellular stimulating effect like that of sis protein (Yamamoto et al, 1991;Nakanishi et al, 1992), i.e. the presence of basic FGF protein in the nucleus has raised the possibility of specific nuclear functions for this molecule in addition to signalling at the cell surface (Mason, 1994 Follow-up (months) studies suggesting the importance of contacts between tumour cells and fibroblasts (Tanaka et al, 1988;Coucke et al, 1992;Gartner et al, 1992).…”
Section: Discussionmentioning
confidence: 56%
“…FGF-2 has been implicated in transcription regulation. 33,34 In particular, FGF-2 is known to activate various transcription factors 35 and regulates the serum response factor (SRF) promoter. 36 However, it has also been demonstrated that FGF could regulate the alternative splicing of FGF receptor 2 and 3 (FGFR-2 or -3).…”
Section: Discussionmentioning
confidence: 99%